2016
DOI: 10.1080/15548627.2016.1159377
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy is required for ectoplasmic specialization assembly in sertoli cells

Abstract: The ectoplasmic specialization (ES) is essential for Sertoli-germ cell communication to support all phases of germ cell development and maturity. Its formation and remodeling requires rapid reorganization of the cytoskeleton. However, the molecular mechanism underlying the regulation of ES assembly is still largely unknown. Here, we show that Sertoli cell-specific disruption of autophagy influenced male mouse fertility due to the resulting disorganized seminiferous tubules and spermatozoa with malformed heads.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(97 citation statements)
references
References 66 publications
3
94
0
Order By: Relevance
“…However, Sertoli cells also provide the nutrients and regulatory factors for supporting all phases of germ cell development and maturity when they lose their proliferative ability in mature testis (Chojnacka, Zarzycka, & Mruk, ; Dimitriadis et al., ; Gerber, Heinrich, & Brehm, ). Accumulating evidence has shown that autophagy can guarantee the normal functional role to support germ cell development and maturity through degradation of the PDLIM1 protein or degradation of ingested cell‐derived substrates (Liu et al., ; Yefimova et al., ). Based on these above‐mentioned clues, we aimed to investigate the regulation mechanisms of miR‐26a in swine Sertoli cell autophagy in this study.…”
Section: Introductionmentioning
confidence: 99%
“…However, Sertoli cells also provide the nutrients and regulatory factors for supporting all phases of germ cell development and maturity when they lose their proliferative ability in mature testis (Chojnacka, Zarzycka, & Mruk, ; Dimitriadis et al., ; Gerber, Heinrich, & Brehm, ). Accumulating evidence has shown that autophagy can guarantee the normal functional role to support germ cell development and maturity through degradation of the PDLIM1 protein or degradation of ingested cell‐derived substrates (Liu et al., ; Yefimova et al., ). Based on these above‐mentioned clues, we aimed to investigate the regulation mechanisms of miR‐26a in swine Sertoli cell autophagy in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Unwanted distribution of TBCs directly impaired the function of Sertoli cells as well as the communication between Sertoli cells and germ cells. Liu et al suggested that the different influences of autophagy on apical ES and TBCs assembly might come from their different F-actin arrangements, because F-actin is packed in hexagonal arrays in the ES, while it appears as an embranchment surrounding the tubular portion of TBCs [36,58,59]. Furthermore, the incorrect distribution of TBCs might also be resulted from the abnormal structure of apical ES or the malformation of sperm head, whereas these possibilities still remain to be uncovered by further experimental data.…”
Section: Autophagy Is Required For Structural Modulation In Sertoli Cellmentioning
confidence: 99%
“…Successful organization of cytoskeleton in Sertoli cell is highly related to the produce of functional spermatozoa. The accumulation of PDLIM1 disrupts the F-actin hoops of the apical ES and related microtubule-based structures in the seminiferous epithelium, which ultimately leading to the disruption of Sertoli cell-germ cell communication thereafter contributing to the malformation of sperm head [36].…”
Section: Autophagy Is Required For Structural Modulation In Sertoli Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunofluorescence and immunohistochemical assays were performed as previously described (19). For IF staining of human sperm, semen was spread on polylysine-coated slides and dried in air, then fixed with 4% PFA and stained with FITC-PNA for acrosomes and DAPI for DNA.…”
Section: Immunofluorescence (If)mentioning
confidence: 99%